ANALISIS KINERJA KEUANGAN PADA KOPERASI PEGAWAI REPUBLIK INDONESIA BINA RAHARJA KECAMATAN CERME PERIODE 2007 -2011 - ANDIS SYARIFUDIN (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
Aim from this research was to measure the performance of finance KPRI Bina Raharja Cerme be surveyed from liquidity aspect, activity, leverage, and profitability. Cooperation finance performance measuring to be done to use analysis ratio of finance like: liquidity aspect to cover ratio liquidity. activity Aspect to be measured with Turn Over Asset (ATO). Leverage Aspect to be measured with Solvability Ratio. Profitability Aspect to be measured with Return on Total Assets (ROA) and Profitability ratio. data analysical Method that be used is Time Series Analysical. From analysiical result knew that liquidity ratio good less cooperation with average the ratio 387,17%. Enough Activity Ratio good because cooperationhas ability to create the the high sale level each annual with average 1,16 times rotation. Leverage Ratio that to be measured with solvability good less valuable because average each annual to reach 196,49% (Less, because more than130% standard Minister Cooperation). ROA has value 8,30% and profitability has value 35,73%. Its mean the cooperation ability to result profit very good.